2012
DOI: 10.1542/peds.2010-3302
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Analysis of Quality Indicators for Children Treated in the Emergency Department for Asthma

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Studies of the association between process and outcome measures of the quality of acute asthma care for children have been mixed. These studies are limited by small, single-institution settings or by examining the association at the aggregate level. WHAT THIS STUDY ADDS:This first multicenter analysis of the process-outcome association in acute asthma care for children revealed no association. Because the validity of process measures depends on association with outcomes, further s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…For example, while a low chest X‐ray rate in asthma may be an indicator of quality, a much more comprehensive view of quality of care for asthma is gained by combining this measure with measures of admission, steroid administration and representation rates. Similar findings for the management of febrile convulsions and gastroenteritis have been demonstrated …”
Section: Practical Implementationsupporting
confidence: 80%
See 1 more Smart Citation
“…For example, while a low chest X‐ray rate in asthma may be an indicator of quality, a much more comprehensive view of quality of care for asthma is gained by combining this measure with measures of admission, steroid administration and representation rates. Similar findings for the management of febrile convulsions and gastroenteritis have been demonstrated …”
Section: Practical Implementationsupporting
confidence: 80%
“…Many of these measures deteriorate with departmental crowding. Two recent studies have been unable to identify outcome change associated with improvements in process measures of time to bronchodilator and systemic corticosteroid …”
Section: Effectiveness and Efficiencymentioning
confidence: 99%
“…34 This approach has been used in prior studies of both acute and chronic asthma to adjust for this type of confounding. 14,[35][36][37] Lastly, our study population consisted of adults who presented mainly to academic EDs. Therefore our inferences might not be generalizable to children or asthma management in nonacademic EDs, where emergency asthma care might be better or worse than in our participating EDs.…”
Section: Potential Limitationsmentioning
confidence: 99%
“…Process measures are designed to examine concordance with expected care and, when provided, should lead to improved health outcomes . However, previous studies of process–outcome link in the quality of ED acute asthma care have reported inconsistent associations with acute outcomes . For example, a retrospective analysis of Canadian ED‐based data reported that the hospitalization rate of children treated in the EDs with standardized protocols was no different from the rate of children in EDs without these protocols .…”
Section: Discussionmentioning
confidence: 99%
“…To implement process measures as performance metrics, greater concordance should lead to improved patient outcomes . To date, studies of the process–outcome link in the quality of ED acute asthma care have focused on risks of hospitalization . For instance, several studies have demonstrated that delivery of guideline‐concordant asthma care in the ED is associated with a reduced hospitalization rate .…”
mentioning
confidence: 99%